Sleep Power Spectral Density and Spindles in PTSD and Their Relationship to Symptom Severity - Denis, Dan; Bottary, Ryan; Cunningham, Tony J.; Zeng, Shengzi; Daffre, Carolina; Oliver, Kaitlyn L.; Moore, Kylie; Gazecki, Samuel; Kram Mendelsohn, Augustus; Martinez, Uriel; Gannon, Karen; Lasko, Natasha B.; et al. (Frontiers in Psychiatry, 2021)
Sleep disturbances are common in posttraumatic stress disorder (PTSD), although which sleep microarchitectural characteristics reliably classify those with and without PTSD remains equivocal. Here, we investigated sleep microarchitectural differences (i.e., spectral power, spindle activity) in trauma-exposed individuals that met (n = 45) or did not meet (n = 52) criteria for PTSD and how these differences relate to post-traumatic and related psychopathological symptoms. Using ecologically-relevant home sleep polysomnography recordings, we show that individuals with PTSD exhibit decreased beta spectral power during NREM sleep and increased fast sleep spindle peak frequencies. Contrary to prior reports, spectral power in the beta frequency range (20.31-29.88Hz) was associated with reduced PTSD symptoms, reduced depression, anxiety and stress and greater subjective ability to regulate emotions. Increased fast frequency spindle activity was not associated with individual differences in psychopathology Our findings may suggest an adaptive role for beta power during sleep in individuals exposed to a trauma, potentially conferring resilience. Further, we add to a growing body of evidence that spindle activity may be an important biomarker for studying PTSD pathophysiology.